A formative evaluation: co-designing tools to prepare vulnerable young people for participating in technology development - Mildenberger Tabea; Schmidt Marc; Zorn Isabel (i-com)
Participatory processes are key for designing technology solutions but challenging since target groups rarely have technological expertise. They are, however, experts in their lives. Vulnerable young people are even more challenged when asked to participate. A toolkit approach can introduce non-tech-savvy individuals to digital technology. This paper presents the process of (co-)designing a toolkit for vulnerable young people and social workers. The evaluation provides insights into what components are needed to prepare for participatory technology development. The toolkit can be seen as a mobile laboratory that supports technology development and builds on considerations from other research and design processes. The toolkit was (co-)designed in two phases. An initial version based on other prototypes and the state of the art was evaluated according to feedback from social work professionals. The revised version was evaluated by both professionals and vulnerable young people, leading to refinement and final redesign. The final toolkit, focusing on the smart home domain, was evaluated through participant observation and qualitative content analysis. The results show how feedback, inductively derived in four categories, led to the design of the toolkit with three modules relevant to engaging vulnerable young people in technology design: experience, understand and co-design.